A rhetorical analysis of South African presidents' state of the nation addresses post-1994 - Nkosi, Robson Siphosihle (University of the Free State, 2024)
In South Africa, a State of the Nation Address (SONA) is considered an important speech in the nation’s political calendar. As notable and consequential as the SONA is, it remains a limitedly explored research avenue, especially from a dramatistic criticism point of view. This dramatistic criticism study was conducted to bridge this gap by unveiling and developing an in-depth understanding of the underlying motive behind each democratically elected South African President’s first State of the Nation Addresses post-apartheid. The study employed a pentadic analysis approach owed to Kenneth Burke (Cholid et al., 2019) to analyse a corpus of four purposively selected State of the Nation Addresses. The findings suggested the pentadic element Scene as the motive behind all the analysed State of the Nation Addresses. However, the label for the pentadic element Scene slightly varied across the four SONA speeches. Consequently, the study concludes that the underlying motive behind each democratically elected South African President’s first State of the Nation Address was to induce cooperation of the SONA audiences in addressing the sociopolitical and economic challenges of the state post-apartheid.
Dissertation(M.A.(Communication Science))--University of the Free State, 2024
Keywords: Rhetorical criticism; SONA; Rhetorical analysis; Rhetoric